Solid Foundation, Teacher’s Competency, and Learner Support as Determinants of Learners’ Interest in Learning Geometry - Zinge, Vuyolwethu; Chiphambo, Shakespear Maliketi (Urogram Studi Pendidikan Matematika, Universitas Ivet, 2025)
The study aimed to explore the relationship between a solid foundation in geometry and learners' interest in learning geometry, the extent to which teacher competency influences learners' interest in learning geometry and how the availability of learner support impacts learners' interest in learning geometry. The study employed a theoretical framework combining the Social Cognitive Theory, Self-Determination Theory, and the Conceptual Change Model as the lens to analyse the collected data on the topic. The study employed a theoretical framework combining the Social Cognitive Theory, Self-Determination Theory, and the Conceptual Change Model as the lens to analyse the collected data on the topic. The study employed a systematic sampling technique to select 60 learners (20 from each of the selected schools in the circuit, (Grade 10= 26 and Grade 11= 34). From the cohort of 420. After testing the three null hypotheses, each at 0.05 significance level, H0: There is no significant relationship between the combined effects of solid foundation and learner support on learners' interest in learning geometry. One was accepted, H0: No significant relationship exists between a teacher’s geometry competence and learners' interest in geometry. To improve support mechanisms, for example, creating mentoring programs, offering additional tutoring or assistance, providing resources for self-directed learning, or fostering a supportive learning environment.